School climate: the impact on the dropout issue among secondary school students in Malaysia / Menegaa Paraman and Rosila Bee Mohd Hussain - Paraman, Menegaa; Mohd Hussain, Rosila Bee (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The role of the school's climate is crucial in producing disciplined and well performing students in the aspect of learning in schools because education is an important platform in driving quality human resources for the future of the country. Therefore, this study focuses on the role of the school's climate that affects students to dropout in secondary schools in Malaysia. This qualitative study research findings are presented accurately through three levels such as categorising and arranging data in analytical tables and quotes; triangulation and data coding techniques; and identifying themes to give meaning on the issue of school dropouts. The findings are presented in narrative compilation. The study found that the highest dropout rates were at lower secondary levels. The most dominant factor that contributed to students' dropout issue was the influence of friends (peer factor) in school and outside of schools followed by poor academic performances by students, including disciplinary problems and bullying among students. The study also found that the creation o f a safe and effective learning environment within the school climate is very important to ensure academic success and disciplinary practices among students. The study highlights that the school's climate including management and teaching and learning system should be reviewed for the future of young people to be able to succeed in their lives and be committed to the nation's social and economic development. The study also emphasized potential strategies as a precautionary fortress on school student’s dropout issues and to avoid the existence of risky students in school environments especially in secondary schools. This study focuses on the importance of the education sector in preparing each student to meet future challenges and to lead society and the nation in upcoming years.